Determination of Total Flavonoid of Ethanol Extract of Pegagan Leaves (Centella asiatica (L.) Urb) Using Maceration and Soxhletation Methods - Wahyudi, Muhammad; Manik, Umi Chairani; Ridwanto, Ridwanto; Daulay, Anny Sartika; Rahmadani, Rahmadani (Indonesian Journal of Science and Pharmacy, 2024)
A study was conducted to determine the total flavonoid content of ethanol extract of pegagan leaves (Centella asiatica (L.) Urb) using maceration and soxhletation methods. The study began with the preparation of pegagan leaf simplicia and its characterization, preparation of ethanol extract by maceration and soxhletation, phytochemical screening and determination of total flavonoid content of ethanol extract of pegagan leaves using visible spectrophotometry method. The results of phytochemical screening of ethanol extract of pegagan leaves indicated the presence of alkaloid, flavonoid, saponin, tannin, steroid/triterpenoid and glycoside compounds. The results of determining the total flavonoid content in ethanol solvent extract by maceration were 31.6416±0.1534 mgQE/g and ethanol solvent extract by soxhletation were 20.832±0.0514 mgQE/g. Extraction of pegagan leaves by maceration method was more effective than soxhletation method.